New technologies to improve bycatch mitigation in industrial tuna fisheries. Issue 3 (1st December 2021) - Poisson, François; Budan, Pierre; Coudray, Sylvain; Gilman, Eric; Kojima, Takahito; Musyl, Michael; Takagi, Tsutomu
Abstract: For many years, tremendous effort has been dedicated to developing new industrial tuna fisheries, while their adverse impacts on threatened marine species have received relatively little attention. In tuna fisheries, bycatch is the major anthropogenic threat to marine megafauna in general, particularly sharks. Research on the development of gear technology for bycatch reduction and potential mitigation measures helped tuna Regional Fisheries Management Organizations adopt bycatch reduction management measures. After reviewing past research on the development of mitigation measures for pelagic longline and tropical purse seine fisheries based on pelagic species' behaviours, we describe promising new approaches integrating recent technological breakthroughs. New innovations include autonomous underwater vehicles carrying cameras along with miniaturized sensors, aerial drones, computer simulation of fishing gear geometry, environmental DNA assays, computer visualizations and deep learning. The successful application of such tools and methods promises to improve our understanding of factors that influence capture, escape and stress of caught species. Moreover, results emerging from recent ethological research explaining the power of social connection and learning in the "fish world" such as social learning from congeners, habituation to deterrents, and how past fishery interactions affect responses to fishing gear should be taken into account when developing technical mitigation measures.